The RELIABILITY AND ACCURACY OF EPICAM M AND RETCAM SHUTTLE COMPARED TO INDIRECT OPHTHALMOSCOPE IN DETECTION OF RETINOPATHY OF PREMATURITY - Angky, Meiliaty Ariesta; Akib, Marliyanti N; Syamsu, Noor; Ichsan, Andi Muhammad; Muhiddin, Habibah S; Alasiry, Ema (Indonesian Vitreoretinal Society, 2023)
Introduction: In this study, we reported the performance of 2 retinal camera types on premature infants in Retinopathy of Prematurity (ROP) screening. Methods: Premature infants went through : (1) examination by a pediatric ophthalmologist using indirect ophthalmoscopy as a standard of reference; (2) digital imaging by a photographer using EpiCam M and RetCam shuttle. After a month, images were interpreted randomly and single-blinded by the same pediatric ophthalmologist (grader). Result: A total of 44 eyes from 22 premature infants were included in this study (ROP 11 subjects and non-ROP 11 subjects). Detection of ROP with EpiCam M had a moderate agreement (Kappa 0.502, p 0.009) and very good agreement with RetCam shuttle (Kappa 0.862, p <0.0001). Sensitivity, specificity, and accuracy of EpiCam M in detection of ROP were 80.95%, 69.56%, and 75%; RetCam shuttle 85.71%, 100%, and 93.18% respectively. Conclusion: Both EpiCam M and RetCam shuttle displayed significant agreement with indirect ophthalmoscope in detecting ROP. EpiCam M can potentially be allowed to be a viable low-cost alternative device for ROP screening in low resource environments but should be noted that EpiCam M has a high false positive rate which affects its specificity and accuracy rate. Some issues also need to be considered if using epiCam M in telemedicine includes frequent glare and longer duration of documentation